Pengaruh Sulfat Terhadap Kuat Tekan Beton Dengan Variasi Bubuk Kaca Substitusi Sebagian Pasir Dengan W/C 0,4 dan 0,5 - Nety .; Gunawan Tanzil (Jurusan Teknik Sipil Fakultas Teknik Universitas Sriwijaya, 2013)
The Concrete buildings which located in certain location susceptible to sulfate attack. The sulfate can damage the buildings, one of the alternative that can be used to improve the durability of concrete due to sulfate attack by reducing the porosity, the glass powder as a sample that can be use. The glass powder has a pozolanic character that can fill the empty voids in the concrete. The purpose of this study was to determine the effect of glass powder as fine aggregate replacement in concrete that exposed and not exposed to sulfate attack. In this research, some tests were done to determine the compressive strength by replacing sand with 0%, 5%, 10%, 15% and 20% of glass powder. The cylinder specimen was soaked with plain water and Â 5% MgSO4 solution with 7, 21 and 28 days, using water-cement ratio 0,4 and 0,5. TheÂ result shows that the smallest percentage reduction in the compressive strength due to sulfate attack was founded in 20% of glass content, for w/c = 0,4 in 7 days was 0,57% and for w/c = 0,5 was 1,45%., The highest compressive strength of concrete that was soaked with plain water and 5% MgSO4 solution was founded in 20% of glass content, for w/c = 0,4 in 28 days was 44,72 MPa and 43,85 MPa and then for w/c = 0,5 was 37,80 MPa and 36,45 MPa. So if the content of glass increase the compressive strength will increase and the percentage reduction in compressive strength due to sulfate attack will decrease. Â Keywords: glass powder, compressive strength, sulfate.